How to increase learning motivation using hypnotherapy - Dermawan, Oki; Busmayaril, Busmayaril; Defriyanto, Defriyanto; Rozi, Fachrur (Universitas Islam Negeri Raden Intan Lampung, 2021)
Each individual must have different motivation to learn, some are low, and some are high. Students' motivation to learn can be expressed from outside or within the individual. The result of low learning motivation is not being excited during the learning process. Low learning motivation can work for anyone. This problem occurs in 29 State Junior High School, Bandar Lampung students experience low learning motivation with characteristics such as chatting, sleeping, not paying attention while in the learning process. So it is necessary to increase the motivation to learn by using hypnotherapy. This study aims to reveal the effect of hypnotherapy on learning motivation, followed by students. This research is quantitative with a Quasi-Experimental research type, and One group pretest-posttest design research design. The results show the difference between before and after being given hypnotherapy. So it can be denied that hypnotherapy affects learning motivation in students. Hypnotherapy can arouse students' enthusiasm in learning and can suggest various positive things that aim to increase self-confidence, motivation, and a positive self-image.